Low bandwidth laser doppler blood flowmetry - Carpenter, James (2014)
Laser Doppler Blood Flowmetry (LDBF) has for several decades been applied to measure the flow of red blood cells in living tissue. Laser Doppler Perfusion Imaging (LDPI), a recent advancement which enables full-field blood flow visualisation, is gaining clinical acceptance in fields such as burn diagnostics.